Herpes zoster and the search for an effective vaccine. (25th July 2016) - Arnold, N.; Messaoudi, I.
Summary: Primary infection with varicella zoster virus (VZV), an exclusively human neurotrophic alphaherpsesvirus, results in varicella, known more commonly as chickenpox. Like other alphaherpesviruses, VZV establishes latency in the sensory ganglia and can reactivate to cause herpes zoster (also known as shingles), a painful and debilitating disease, especially in elderly and immunocompromised individuals. The overall incidence of herpes zoster in Europe and the United States is three per 1000 people, but increases sharply after 60 years of age to 10 per 1000 people. Zostavax ® is a vaccine approved by the Federal Drug Administration for the prevention of herpes zoster. Unfortunately, this vaccine reduces the incidence of disease by only 51% and the incidence of post‐herpetic neuralgia by 66·5% when administered to those aged 60 and older. Moreover, it is contraindicated for individuals who are immunocompromised or receiving immunosuppressant treatments, although they are at higher risk for herpes zoster compared to immune‐competent older individuals. This paper reviews VZV pathogenesis, host responses and current vaccines available to prevent herpes zoster. Abstract : Herpes Zoster is a painful and debilitating disease caused by the reactivation of Varicella Zoster Virus (VZV), the causative agents of chicken pox. This review summarizes our current understanding of the virus life cycle, the immune response during both chickenpox and herpes zoster. We then review vaccines against herpes zoster that have been approved and those that are in the pipeline. Finally, we discuss animal models that can be used to develop novel vaccine strategies and gain additional insight into interactions between host and VZV.